2018
DOI: 10.1128/iai.00958-17
|View full text |Cite
|
Sign up to set email alerts
|

Differential In Vitro Cytokine Induction by the Species of Cryptococcus gattii Complex

Abstract: Cryptococcal species vary in capsule and cell size, thermotolerance, geographic distribution, and affected populations. and affect mainly immunocompetent hosts; however, ,, and cause infections mainly in immunocompromised hosts. This study aimed to compare the capacities of different species of the species complex to induce cytokines and antimicrobial molecules in human peripheral blood mononuclear cells (PBMCs). and induced the lowest levels of tumor necrosis factor alpha (TNF-α), interleukin-1β (IL-1β), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…The remaining three - IL-1ra, LIF, and HGF—are important in the regulation of inflammation. If the cytokine downregulation can be attributed to the direct action of the fungus remains to be determined but C. neoformans capsule polysaccharide has been previously implicated in cytokine downregulation in human monocytes (Vecchiarelli et al, 1995) while C. gattii downregulates the expression of antimicrobial peptide, cathelicidin, in human PBMCs (Herkert et al, 2018). Interestingly, in a previous study, we measured the response of MCs to C. albicans and detected a very different pattern of cytokine release (Lopes et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining three - IL-1ra, LIF, and HGF—are important in the regulation of inflammation. If the cytokine downregulation can be attributed to the direct action of the fungus remains to be determined but C. neoformans capsule polysaccharide has been previously implicated in cytokine downregulation in human monocytes (Vecchiarelli et al, 1995) while C. gattii downregulates the expression of antimicrobial peptide, cathelicidin, in human PBMCs (Herkert et al, 2018). Interestingly, in a previous study, we measured the response of MCs to C. albicans and detected a very different pattern of cytokine release (Lopes et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In short, 20 last instar larvae of Galleria mellonella weighing 230–330 mg without any grey marks were injected with 10 6 cryptococci per animal in PBS, as previously described [ 13 ]. Two Cryptococcus isolates, known to be highly-virulent (R265) and avirulent (CBS7750) in a mouse model [ 14 ], were used as comparators. Infected animals were incubated at 37 °C for 9 days and checked daily for survival (movement upon stimulation).…”
Section: Case Report and Resultsmentioning
confidence: 99%
“…Unlike C. deuterogattii (VGII), which causes outbreaks related to few hypervirulent clones, clinical isolates of C. bacillisporus (VGIII) have a higher genetic diversity [ 18 ]. This species induces lower levels of proinflammatory cytokines than other members of the C. gattii complex, leading to prolonged survival and chronic infections [ 14 ]. Two main subgroups have been recognized using different techniques; VGIIIa and VGIIIb by multilocus sequence typing [ 20 ] and serotypes B and C by restriction fragment length polymorphism (RFLP) analysis of the CAP59 gene [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a rebuttal, Hagen et al defended the nomenclature changes and noted that the main advantage will be the advancement of the field through stimulation of further studies to assess for similarities and differences between the recognized species [66]. Additional work has subsequently reported that the newly proposed Cryptococcus species may indeed have clinically significant differences [23,66,110,111]. However, many clinical microbiology laboratories may not be able to adapt to the new nomenclature into their routine workflow in the near future, as the new species are not yet incorporated into commercially available assays and databases cleared for clinical use by regulatory agencies for diagnosis or species identification.…”
Section: Clinically Relevant Changes In Fungal Nomenclature and Cumentioning
confidence: 99%